Engagement of cortico-cortical and cortico-subcortical networks in a patient with epileptic spasms: An integrated neurophysiological study. Issue 9 (September 2020) - Inoue, Takeshi; Kobayashi, Katsuya; Matsumoto, Riki; Inouchi, Morito; Togo, Masaya; Togawa, Jumpei; Usami, Kiyohide; Shimotake, Akihiro; Matsuhashi, Masao; Kikuchi, Takayuki; Yoshida, Kazumichi; Kawawaki, Hisashi; et al.
Highlights: We applied integrated neurophysiology to investigate epileptic network activity during epileptic spasms (ES). Neurophysiological techniques revealed the engagement of cortico-cortical and subcortical networks. Pathways other than the direct descending pathway from the positive motor area may be important in the generation of ES. Abstract: Objective: We aimed to delineate the engagement of cortico-cortical and cortico-subcortical networks in the generation of epileptic spasms (ES) using integrated neurophysiological techniques. Methods: Seventeen-year-old male patient with intractable ES underwent chronic subdural electrode implantation for presurgical evaluation. Networks were evaluated in ictal periods using high-frequency oscillation (HFO) analysis and in interictal periods using magnetoencephalography (MEG) and simultaneous electroencephalography, and functional magnetic resonance imaging (EEG-fMRI). Cortico-cortical evoked potentials (CCEPs) were recorded to trace connections among the networks. Results: Ictal HFO revealed a network comprising multilobar cortical regions (frontal, parietal, and temporal), but sparing the positive motor area. Interictally, MEG and EEG-fMRI revealed spike-and-wave-related activation in these cortical regions. Analysis of CCEPs provided evidence of connectivity within the cortico-cortical network. Additionally, EEG-fMRI results indicate the involvement of subcortical structures, such as bilateral thalamus (predominantly right) and midbrain. Conclusions: In this case study, integrated neurophysiological techniques provided converging evidence for the involvement of a cortico-cortical network (sparing the positive motor area) and a cortico-subcortical network in the generation of ES in the patient. Significance: Cortico-cortical and cortico-subcortical pathways, with the exception of the direct descending corticospinal pathway from the positive motor area, may play important roles in the generation of ES.